Efek Mediasi Profitabilitas: Modal Intelektual, Diversifikasi Pendapatan dan Nilai Perusahaan - Windie Yustyarani; Indah Yuliana (Esensi: Jurnal Bisnis dan Manajemen, 2020)
This study aims to examine and analyze the effect of intellectual capital and income diversification on firm value mediated by profitability. This study uses secondary data from annual reports on banks listed on the Indonesia Stock Exchange in 2013-2018. There are 30 banking samples in this study based on established criteria (purposive sampling). Data analysis using the WarpPLS 6.0 program. The results shows that intellectual capital had a positive effect on profitability and on company value, income diversification had a negative effect on profitability, while it was found to have no effect on company value, profitability had a positive effect on company value, intellectual capital had an indirect effect on firm value mediated by profitabilit with partial mediation, while mediation is not supported by the indirect effect of Diversification of Revenue on Company Value.